2007
DOI: 10.1111/j.1365-2222.2007.02856.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between early intestinal colonization, mucosal immunoglobulin A production and systemic immune development

Abstract: 'Favourable' colonization, particularly with bifidobacteria, was associated with effects on cellular immune function, but this was not associated with mucosal immunity (secretory IgA) or reduced risk of allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 30 publications
2
36
0
2
Order By: Relevance
“…The diversity of the neonatal microflora is influenced by many antenatal and postnatal factors, including maternal vaginal and gastrointestinal flora, mode of delivery, GA, nutritional source (parenteral feeding, human milk, formula), and antibiotic exposure [15,16,17]. The establishment of intestinal microbiota provides a source of microbial stimulation that drives postnatal maturation of the immune system and promotes development of adaptive immunity [18,19,20]. Antibiotic exposure at birth is thought to alter this normal immune maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of the neonatal microflora is influenced by many antenatal and postnatal factors, including maternal vaginal and gastrointestinal flora, mode of delivery, GA, nutritional source (parenteral feeding, human milk, formula), and antibiotic exposure [15,16,17]. The establishment of intestinal microbiota provides a source of microbial stimulation that drives postnatal maturation of the immune system and promotes development of adaptive immunity [18,19,20]. Antibiotic exposure at birth is thought to alter this normal immune maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that bifidobacteria can be used as an immune response moderator [11][12][13][14][15] and these studies have been focused on its anti-tumor activity [16][17][18][19][20][21]. But there has been no report on its anti-tumor effect when used as a vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The influences are primarily driven by changes in the gastrointestinal microbiota associated with feeding and early childhood infections and immunizations. However, supplementation with Lactobacillus acidophilus from birth did not influence the pattern of development of salivary IgA, despite different colonization patterns, compared to a placebo group (Martino et al, 2008), with both groups also having similar allergic sensitization patterns.…”
Section: Nutrition and Dietmentioning
confidence: 91%